Chinese expert recommendations on management of hepatocellular carcinoma during COVID-19 pandemic: a nationwide multicenter survey. Issue 3 (March 2022) - Zhao, Hong; Zhou, Aiping; Zhou, Jianguo; Bi, Xinyu; Yan, Shida; Jin, Jing; Wei, Wenqiang; Li, Muxing; Gong, Caifeng; Chen, Qichen; Luo, Zhiwen; Li, Ning; et al.
Abstract: Background: This study aimed to investigate the work status of clinicians in China and their management strategy alteration for patients with hepatocellular carcinoma (HCC) during the COVID-19 pandemic. Methods: A nationwide online questionnaire survey was conducted in 42 class-A tertiary hospitals across China. Experienced clinicians of HCC-related specialties responded with their work status and management suggestions for HCC patients during the pandemic. Results: 716 doctors responded effectively with a response rate of 60.1%, and 664 were included in the final analysis. Overall, 51.4% (341/664) of clinicians reported more than a 60% reduction of the regular workload and surgeons declared the highest proportion of workload reduction. 92.5% (614/664) of the respondents have been using online medical consultation to substitute for the "face-to-face" visits. Adaptive adjustment for the treatment strategy for HCC was made, including the recommendations of noninvasive and minimally invasive treatments such as transcatheter arterial chemoembolization for early and intermediate stage. Targeted therapy has been the mainstay for advanced stage and also as a bridge therapy for resectable HCC. Discussion: During the COVID-19 pandemic, online medical consultation is recommended to avoid social contact. Targeted therapy as a bridge therapy is recommended for resectable HCC considering the possibility of delayed surgery.